Towards a relational governance of internal stakeholders in non-profit organisations (NPOs): When commitment is not enough - Plaisance, Guillaume (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
The engagement of internal stakeholders in nonprofit organizations is a crucial resource for their functioning. The disengagement context finds a response through stakeholder governance and its spontaneous and specific mechanisms. These mechanisms are based on the quality of the relationship with stakeholders and its components (trust, satisfaction, influence, engagement) and play a role in understanding the success of grassroots volunteer organizations (GVOs). A study carried out within the “Young Farmers” union allows to verify the relevance of these mechanisms. The results contribute to the resource dependency theory, but also highlight the importance of a strategic differentiation based on the stakeholders.